2021
DOI: 10.3390/jmse9060601
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability Analysis of the Riumar Dune Field in El Garxal Coastal Wetland (Ebro Delta, Spain)

Abstract: The aim of this work is to apply a vulnerability index in the dune field located in the Riumar urban zone at the mouth of the Ebro River. This dune field represents the natural barrier of the El Garxal coastal lagoon system. The index used integrates the dimensions of exposure, susceptibility, and resilience from the analysis of 19 variables. The results obtained show moderate susceptibility and high resilience, which are in line with the behavior of this dune field during the last sea storms (Gloria in Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
(78 reference statements)
0
0
0
Order By: Relevance
“…Recent studies suggested an increasing trend in storm wave intensity in the western Mediterranean [63]. Comprehending the effects of marine storms on Mediterranean coastal wetlands, marshes, and lagoons is vital to developing precise adaptation procedures [64,65]. The use of space research and optical satellite imagery can assist in developing operational coastal flood awareness systems at the local, regional, and national scales, complementing the current framework for large transnational river systems after extreme events or natural hazards.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested an increasing trend in storm wave intensity in the western Mediterranean [63]. Comprehending the effects of marine storms on Mediterranean coastal wetlands, marshes, and lagoons is vital to developing precise adaptation procedures [64,65]. The use of space research and optical satellite imagery can assist in developing operational coastal flood awareness systems at the local, regional, and national scales, complementing the current framework for large transnational river systems after extreme events or natural hazards.…”
Section: Discussionmentioning
confidence: 99%